Tuberculous pleurisy. - Enarson, D. A. (1982)
A review of the records for all cases of tuberculous pleurisy notified in Canada from 1970 through 1974 and in British Columbia from 1967 through 1976 showed that in the periods studied the annual incidence of this condition was low, just under nine cases per million population, and was declining. The disease commonly occurred a few months after a primary infection with tubercle bacilli. Bacteriologic confirmation of the diagnosis was possible in only 40% of the cases since biopsy specimens were not consistently cultured.